Visual arts management - Taylor, Jeffrey, 1968- (Mastering management in the creative and cultural industries., 2018)
"The arts sector is of vital importance to the global economy and students aspiring to a career in the visual arts are increasingly required to gain an understanding of the business side of the arts world. This textbook introduces the field of arts management with a focus on visual arts. Visual Arts Management provides the first comprehensive textbook to the art business. The book covers the full range of the art world from contemporary galleries, secondary market, auction houses, art fairs, and museums. Topics include overviews of the distinct sectors of the business, but also delves in to technical topics: curatorship, antiques, cultural heritage compliance, marketing, art criticism, taxation, customs, insurance, transportation, appraising, conservation, and connoisseurship. Each chapter concludes with a real-world case study to provide cautionary tales of the dangers and pitfalls of the art business. This unique textbook, authored by an experienced instructor, presents a global perspective on the rapidly developing art business in a way that is relevant for arts management classes and art professionals worldwide."- Resumé vydavatel